FinTech adoption and household risk-taking - Claire Yurong Hong; Xiaomeng Lu; Jun Pan (Bank of Finland, Bank of Finland Institute for Emerging Economies (BOFIT), 2021)
Using a unique FinTech data containing monthly individual-level consumption, investments, and payments, we examine how FinTech can lower investment barriers and improve risk-taking. Seizing on the rapid expansion of offline usages of Alipay in China, we measure individuals' FinTech adoption by the speed and intensity with which they adopt the new technology. Our hypothesis is that individuals with high FinTech adoption, through repeated usages of the Alipay app, would build familiarity and trust, reducing the psychological barriers against investing in risky assets. Measuring risktaking by individuals' mutual-fund investments on the FinTech platform, we find that higher FinTech adoption results in higher participation and more risk-taking. Using the distance to Hangzhou as an instrument variable to capture the exogenous variation in FinTech adoption yields results of similar economic and statistical significance. Focusing on the welfare-improving aspect of FinTech inclusion, we find that individuals with high risk tolerance, hence more risk-taking capacity, and those living in under-banked cities stand to benefit more from the advent of FinTech.
URN:NBN:fi:bof-202110252068
Keywords: G11; G50; 330; FinTech; Digital Payment; Financial Inclusion; Consumption; Risk Taking